Pengaruh Kondisi Makroekonomi Terhadap Jumlah Penerimaan Zakat di BAZNAS - Irawan, Anggi (CV. Civiliza Publishing, 2022)
The purpose of this study was to examine the impact of macroeconomic factors, namely inflation, BI-Rate, profit sharing ratios, exchange rates and the amount of money in circulation (M2) on zakat receipts at the central national amil zakat institution (Baznas). This research is quantitative by using secondary data. The data used comes from BAZNAS, Bank Indonesia and the Financial Services Authority (OJK) from 2014-2018. As well as data were analyzed using multiple linear regression. The results of this study indicate that simultaneously, inflation, BI-Rate, profit sharing ratios, exchange rates and the amount of money in circulation (M2) affect the amount of zakat receipts in Indonesia. But partially, the profit sharing ratio does not affect the amount of zakat receipts in Indonesia. In contrast, inflation, the BI-Rate and the exchange rate have a negative and significant effect. Meanwhile, the amount of money in circulation has a positive and significant effect on zakat receipts at the central national amil zakat agency (BAZNAS) in 2014-2018. Tujuan dari penelitian ini adalah untuk menguji dampak faktor ekonomi makro yaitu inflasi, BI-Rate, nisbah bagi hasil, kurs dan jumlah uang yang beredar (M2) terhadap penerimaan zakat di lembaga amil zakat nasional (Baznas) pusat. Penelitian ini bersifat kuantitatif dengan menggunakan data sekunder. Data yang digunakan bersumber dari BAZNAS, Bank Indonesia dan Otoritas Jasa Keuangan (OJK) dari tahun 2014-2018. Serta data dianalisis menggunakan regresi linier berganda. Hasil penelitian ini menunjukkan bahwa secara simultan, inflasi, BI-Rate, nisbah bagi hasil, kurs dan jumlah uang yang beredar (M2) berpengaruh terhadap jumlah penerimaan zakat di Indonesia. Namun secara parsial, nisbah bagi hasil tidak berpengaruh terhadap jumlah penerimaan zakat di Indonesia. Sebaliknya inflasi, BI-Rate dan kurs memiliki pegaruh negatif dan signifikan. Sedangkan jumlah uang yang beredar berpengaruh positif dan signifikan terhadap penerimaan zakat di badan amil zakat nasional (BAZNAS) pusat tahun 2014-2018.